Examining nurses' understanding and knowledge about preparation for COVID-19 in Ardabil hospitals in Iran - Milad Minehmorad; Reza Nemati-Vakilabad; Mohammad Badpeyma; Alireza Mirzaei (BMC, 2024)
Abstract Aims The purpose of this study was to evaluate the preparedness of Iranian nurses for potential pandemics. Background Nurses play a critical role in managing pandemics. They require adequate training, proper equipment, and organizational support to be well-prepared. Methods A descriptive cross-sectional study was conducted in Ardabil, Iran, from July to September 2023, involving 233 nurses from five hospitals. The number of nurses required for each hospital was calculated based on the proportion of nurses in each hospital. Data was collected through a paper-based form that included information about the participants' demographic characteristics and their level of pandemic preparedness in health services. The collected data was analyzed using descriptive statistics to determine the demographic characteristics and levels of pandemic preparedness. Pearson's test was also conducted to establish a relationship between different dimensions of pandemic preparedness. Results Most participants relied on clinical measures and supported using human resources and environmental methods to curb the transmission of a pandemic. They felt assured in their ability to explain the preventive measures against the pandemic. However, fewer respondents had access to healthcare improvement programs, and only a few worked remotely from home. Conclusions According to our study, 90.1% of nurses believe hand washing is the most effective way to prevent spreading infections. Additionally, healthcare professionals can use various tools to respond to the pandemic, including screening for COVID-19 at work, health and wellness programs, telecommuting, COVID-19 Safe programs, social media, and posters. Nurses need continuous education in hand hygiene, health programs, remote work options, and pandemic-safe programs to control infections, reduce risks, and optimize patient care during the pandemic.